Pig-Islet Xenotransplantation: Recent Progress and Current Perspectives - Zhu, Haitao; Wang, Wanli; Yu, Liang; Wang, Bo (Frontiers in Surgery, 2014)
Islet xenotransplantation is a prospective treatment to bridge the gap between available human cells and needs of patients with diabetes. Pig is the ideal candidate to obtain such available islet cells. However, potential clinical application of pig islet transplantation still faces obstacles such as inadequate yield of high-quality functional islets and xenorejection of the transplants. Adequate amounts of available islets can be obtained based on selection of a suitable pathogen-free source herd and the development of isolation and purification methods. Several studies demonstrated feasibility of successful pre-clinical pig islet xenotransplantation and provided insights and possible mechanisms of xenogeneic immune recognition and rejection. Particularly promising is the achievement of long-term insulin independence in diabetic models by means of distinct islet products and novel immunotherapeutic strategies. Nonetheless, further efforts are needed to obtain much more data on safety and efficacy to translate these findings into clinical practice